Macrocyclic Cu(II) and Co(II) Complexes as Catalysts for Hydroxylation of Phenol with H2O2 - Bi, Jian-Hong; Li, Meng; Chen, Yan (Asian Journal of Chemistry, 2010)
The liquid phase catalytic hydroxylation of phenol to hydroquinone and catechol was carried out in the presence of the tetraaza macrocyclic copper(II) and cobalt(II) complexes using H2O2 as oxidant and water/ethanol as solvent. When the Cu(II) and Co(II) complexes were used as catalysts, 35.5 % phenol conversion was obtained with 42.5 % selectivity to dihydroxy benzene and 33.8 % phenol conversion was obtained with 36.8 % selectivity to diphenol under the optimum reaction conditions.